Fault lines in the Orthodox world: geopolitics, theology, and diplomacy in light of the war in Ukraine - Rimestad, Sebastian; Saggau, Emil Hilton (Palgrave Macmillan, 2025)
"Throughout the past years, the Orthodox world has seen numerous political and theological confrontations. New borders have been shaped by churches and states. This only increased in light of the Russian-backed conflict in Ukraine from 2014 and onwards, which has led to new theological lines of thinking, geopolitical confrontations, and an acute need for diplomatic handling of crisis. At the centre is the Russian Orthodox Church's global role and its effects in Ukraine. The confrontations are born out of a complex entanglement of church politics, theological differences, legal tensions, national allegiances, and the very concrete political and military clashes between nation states. In light of the war in Ukraine, Global Orthodoxy has seen new fault lines in the making. This volume gathers chapters that shed light on these entanglements and their political, theological, and geopolitical consequences. The book is not limited to the Russian-Ukrainian conflict, but also includes papers focusing on other nations, churches, and aspects (theological, theoretical, geopolitical, empirical etc.)"--Amazon.com